Bacterial rhomboid proteases mediate quality control of orphan membrane proteins - Liu, Guangyu; Beaton, Stephen E; Grieve, Adam G; Evans, Rhiannon; Rogers, Miranda; Strisovsky, Kvido; Armstrong, Fraser A; Freeman, Matthew; Exley, Rachel M; Tang, Christoph M (The EMBO journal, 2020)
Although multiprotein membrane complexes play crucial roles in bacterial physiology and virulence, the mechanisms governing their quality control remain incompletely understood. In particular, it is not known how unincorporated, orphan components of protein complexes are recognised and eliminated from membranes. Rhomboids, the most widespread and largest superfamily of intramembrane proteases, are known to play key roles in eukaryotes. In contrast, the function of prokaryotic rhomboids has remained enigmatic. Here, we show that the Shigella sonnei rhomboid proteases GlpG and the newly identified Rhom7 are involved in membrane protein quality control by specifically targeting components of respiratory complexes, with the metastable transmembrane domains (TMDs) of rhomboid substrates protected when they are incorporated into a functional complex. Initial cleavage by GlpG or Rhom7 allows subsequent degradation of the orphan substrate. Given the occurrence of this strategy in an evolutionary ancient organism and the presence of rhomboids in all domains of life, it is likely that this form of quality control also mediates critical events in eukaryotes and protects cells from the damaging effects of orphan proteins.
Keywords: membránové proteiny; Electron Transport; Membrane Proteins; substrátová specifita; Shigella; Shigella sonnei; Endopeptidases; rhomboid; proteolýza; endopeptidasy; membrane protein complexes; transport elektronů; Proteolysis; Protein Domains; Bacterial Proteins; quality control; Substrate Specificity; bakteriální proteiny; proteinové domény; intramembrane proteolysis